The challenges facing development policy and projects implementation in Malawi - Hussein, M. K. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Malawi has introduced numerous policy reforms and projects with the aim to promote development at the national and local level. However, despite the policy reforms and a major influx of donor aid, Malawi remains one of the least developed countries of the world. Effective development policy and projects implementation for sustainable national development is a major concern for both government and development partners. Therefore, this paper examines the major hurdles facing development policy and project implementation in Malawi since the advent of multi-party democracy in 1994. The central argument is that much as effective development policy and project implementation is a function of many factors, the disposition of political and bureaucratic leadership and the lack of capacity in institutions are the major constraints in Malawi. The public bureaucracy is not only politicised, but there is a severe scarcity of skilled labour and finances. In addition, corruption is rampant in both political and administrative circles. The paper concludes that pragmatic strategies which include conducting political leadership and management development programmes, enforcing mechanisms for combating corrupt practices and mobilising resources both human and financial must executed in order to promote efficiency and effectiveness in the development policy and project implementation.
Journal article published in International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Development; Malawi; Policy implementation; Project management; Public bureaucracy; Public administration; Sustainable development -- Malawi; Economic development --Developing countries